2011
DOI: 10.1007/s12185-011-0831-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of adult-onset chronic active Epstein–Barr virus infection: a retrospective analysis

Abstract: We performed a retrospective analysis of patients with adult-onset chronic active Epstein-Barr virus infection (CAEBV). First, we analyzed five patients (aged 28-72) diagnosed at our hospitals with EBV-infected clonally proliferating T cells. Four patients were administered cyclophosphamide/doxorubicin/vincristine/prednisone (CHOP) chemotherapy, but no remarkable decrease of viral load was observed in three of the patients. The other patient died 19 days after initiation of CHOP treatment due to disease progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 24 publications
4
46
0
Order By: Relevance
“…Uveitis can occur in EBV-positive T-cell or NK-cell lymphoproliferative diseases (EBV-T/NK-LPDs), also known as chronic active EBV infection (7). However, this patient could not be with EBV-T/NK-LPDs, as her peripheral blood was negative for the EBV DNA (8, 9). …”
Section: Discussionmentioning
confidence: 89%
“…Uveitis can occur in EBV-positive T-cell or NK-cell lymphoproliferative diseases (EBV-T/NK-LPDs), also known as chronic active EBV infection (7). However, this patient could not be with EBV-T/NK-LPDs, as her peripheral blood was negative for the EBV DNA (8, 9). …”
Section: Discussionmentioning
confidence: 89%
“…29 Furthermore, a recent report demonstrated that adult patients with CAEBV had progressive and more aggressive courses than those of childhood onset cases. 46 Interestingly, patients with CD4 ϩ T-cell infection had shorter survival rates than those with NK infection, whereas clinical categories were not correlated with survival rates. Onset age of patients with CD4 ϩ T-cell infection was high (median, 14.5 years).…”
Section: Ebv-associated T/nk-lpd 683mentioning
confidence: 96%
“…This case was presented as case 17 in our previous analysis of adult-onset CAEBV (6); however, the detailed clinical and neurological findings were not included at that time.…”
Section: Introductionmentioning
confidence: 99%